Accuracy and Quality of YouTube Videos as a Source of Information on Vitiligo - Salah LA; AlTalhab S; Omair A; AlJasser M (Dove Medical Press, 2022)
Louai A Salah,1 Saad AlTalhab,2 Aamir Omair,3 Mohammed AlJasser4 1Dermatology Department, East Jeddah General Hospital, Ministry of Health, Jeddah, Saudi Arabia; 2Dermatology Department, College of Medicine, Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi Arabia; 3Research Unit, College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 4Division of Dermatology, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi ArabiaCorrespondence: Louai A SalahDermatology Department, East Jeddah Hospital, 2277 King Abdullah Road, Al Sulaymaniyah, Jeddah, 22253, Makkah, Saudi ArabiaTel +11 12 232 7555Email loai.salah@gmail.comPurpose: Vitiligo is a skin condition characterized by patchy depigmentation in the skin, affecting not just the physical well-being of patients, but also the mental, emotional, and social aspects of their lives. Social media provides a platform where patients can interact and share experiences, and for physicians and experts to disseminate knowledge on the disease. This study aimed to evaluate the accuracy and overall quality of vitiligo-related content on YouTube.Methods: Thirty videos were screened by relevance according to the inclusion criteria. Videos were categorized as either healthcare or non-healthcare sources, and viewer engagement ratio was calculated for each. Three independent vitiligo experts rated the content using the following assessment tools: DISCERN, Accuracy in Digital-health Instrument (ANDI), and Global Quality Scale (GQS). Lastly, Cronbach's alpha was used to estimate the inter-rater reliability and consistency.Results: Most of the screened videos came from health-care sources (57%). Non-healthcare sources achieved a slightly higher viewer engagement ratio, although the difference is not statistically significant (p = 0.23). DISCERN score was low overall in most videos. However, DISCERN score was higher for health-care sources as compared to non-healthcare sources (30.5 ± 9.4 vs 22.7 ± 4,2, p = 0.009). Scores of ANDI and GQS were higher for health-care sources but not statistically significant. There was a good internal consistency in DISCERN rating among the evaluators (0.86).Conclusion: Our study shows a low overall accuracy and quality of YouTube videos on vitiligo. It is recommended that health-care sources improve their information material in terms of quality and viewer engagement, as very little can be done to prevent non-healthcare sources in publishing their own videos. Efforts in educating the public on making distinction between evidence and non-evidence-based claims should also be taken.Keywords: DISCERN, social media, vitiligo, YouTube